2016
DOI: 10.1002/cncr.30417
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress and health care use among survivors of adolescent and young adult cancer: A cross‐sectional analysis of the National Health Interview Survey

Abstract: AYA cancer survivors are more likely to demonstrate mental distress than individuals without cancer. Nevertheless, few survivors may be receiving professional mental health services. Survivors need greater access to mental health screening and counseling to address the current gaps in care delivery. Cancer 2017;123:869-78. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 52 publications
(151 reference statements)
8
106
1
1
Order By: Relevance
“…26 Other cohorts of AYA’s that were much larger (between N=300 and N=6000) found that AYA’s reported more distress than controls. 2729 These inconsistent findings may be due to differing populations of survivors, methodologies or measures used.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…26 Other cohorts of AYA’s that were much larger (between N=300 and N=6000) found that AYA’s reported more distress than controls. 2729 These inconsistent findings may be due to differing populations of survivors, methodologies or measures used.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…This fact suggests that mental disorders are uniquely burdensome to the young . Receiving a cancer diagnosis during this time can present unique developmental challenges at this particularly vulnerable junction in life …”
Section: Introductionmentioning
confidence: 99%
“…Existing research shows that AYA cancer survivors have a worse quality of life (QoL) than their general population peers, as well as specific problems in areas such as fertility, sexuality, career, and psychological well‐being. The majority of the few studies who examine psychological distress of AYAs with cancer have found that every fourth patient exceeds distress cutoff values during and after medical treatment . Furthermore, AYAs with cancer who have completed medical treatment are more distressed than age‐matched healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…4 AYA patients differ markedly from older patients with cancer with regard to biological and developmental aspects. 6,7 Being sick with cancer during this sensitive time often results in multiple physical, psychological, and psychosocial limitations such as infertility, 8 changes in physical appearance, 9 fatigue, 10 and disruptions in social life and career. 6,7 Being sick with cancer during this sensitive time often results in multiple physical, psychological, and psychosocial limitations such as infertility, 8 changes in physical appearance, 9 fatigue, 10 and disruptions in social life and career.…”
Section: Introductionmentioning
confidence: 99%